Marketing and distribution strategies for international organizations - John C. Pattison; John A. Quelch (Intereconomics, 1979)
Recently international organizations as e.g. the International Monetary Fund or the GATT have increasingly been criticized particularly by developing countries. Even the creation of a kind of super-UNCTAD is under discussion. Other institutions are also subjected to increasing pressure to justify the investments of their sponsors in terms of the “product” which they are offering. What about adequate strategies for the international organizations?
Keywords: 330; Institutions